Techniques for the treatment of keratocyst, review of the literature and case report - Ochoa Moreira, Jorge Andrés (2023)
The odontogenic keratocystic tumor (OKT) or also currently known as odontogenic keratocyst (OK) is a benign pathology derived from the remains of the dental lamina characteristic for possessing variable amounts of desquamated keratin. It usually rises as solitary or with the presence of satellite cysts, the appearance of these satellite cysts is frequently related to the possible recurrence of OK, according to the literature, this recurrence can vary between 0 - 50%. As for the treatment stage of (OKT), it can be mentioned that at present there is a well-defined histological and clinical criterion, which facilitates its recognition and therefore its treatment. According to the literature, there are several treatment procedures that can be classified into non-conservative or radical treatments and conservative treatments accompanied by adjuvant methods. Within the nonconservative or radical treatments, we find en bloc resection, which is the most aggressive way to treat a keratocyst; however, it is the most effective way to avoid recurrence. Within the conservative treatments, marsupialization, decompression, and enucleation with or without adjuvant therapy are described. It is paramount to know how to recognize the different types of treatment for (OKT) since this will be conditioned by multiple factors, such as the location of nearby bone structures and the size of the lesion considering the possible involvement of dental structures. The objective is to seek the lowest-risk treatment possible, which avoids recurrence and finally puts an end to this pathology.